Family-school partnerships: a challenge for Teacher Education - Willemse, T; Thompson, I; Vanderlinde, R; Mutton, T (Taylor and Francis, 2018)
Research has shown that collaboration between educational institutions, teachers and families can influence pupils’ and students’ academic achievements, social development and sense of wellbeing in all levels of education (inter alia Castro et al. 2015; Desforges and Abouchaar 2003; Epstein 2001/2011; Jeynes 2007; Boonk, Geijselaers, Ritzen and Brand-Gruwel, 2018). Therefore, more than two decades ago, Shartrand and colleagues (1997) called for more attention towards teachers’ professional development concerning school collaboration with families. This call has been repeated many times over the years (Epstein and Sanders 2006, Epstein 2013, Evans 2013, Saltmarsh, Barr and Chapman 2014, Willemse et al. 2016). In particular, the lack of preparation of pre-service teachers has been highlighted as being problematic. Epstein and Sanders (2006) concluded a decade after Shartrand and colleagues that despite some progress having been made within initial teacher education (ITE) programmes that it was still the case that few pre-service teachers had access to full courses on Family-school partnerships (FSP). They also noticed that there was a lot of resistance to change within ITE programmes. More recent research has concluded that there remains a lack of attention to FSP in ITE (Epstein 2013; Willemse et al. 2016). As Epstein (2013, 117) emphasises: ‘More professors of education should feel comfortable and competent conducting a comprehensive course using an updated text that includes research readings, topics to discuss in class, field experiences, and short and long-term projects’. De Bruïne and colleagues (2014) also describe the struggle of teacher educators to improve the curriculum in times of already overloaded programmes and Evans (2013, see also Willemse et al 2017) in particular notice a lack of attention to FSP in ITE programmes for secondary education.